Daya Dukung Pakan Gajah Sumatera (Elephas maximus sumatranus T, 1847) di Kawasan Pelestarian Plasma Nutfah (KPPN) Hutan Tanaman Industri Ogan Komering Ilir Sumatera Selatan - Aldina Rahmadhani; Zulkifli Dahlan; Indra Yustian (Faculty of Mathtmatics and Natural Sciences, 2018)
PT. Earth Blooms Green (BMH) is a company engaged in the Hutan Tanaman Industri which is lo-cated in South Sumatra, which is part of the area known as the roaming area of Sumatran Ele-phants. PT. Bumi Mekar Hijau have work areas covering 250- 370 hectares. The existence of Sumatran Ele-phants in and around KPPN will be very affected by the carrying capacity of its habitat. A habitat will be able to accommodate a number of wild animals according to the optimum capacity available in the habitat. One im-portant component in habitat support capacity is the availability of feed plants inside or outside forest areas. Types of elephant feed plants found at KPPN PT. BMH consists of Campnosperma macrophylla, Schismatoglottis calyptatra, Dillenia aurea, Shorea beccariana, Diospyros confertiflora, Macaranga pruinosa, Acacia denticulosa, Ficus benjamin, Nephrolepis cordifolia, Pandanus artocarpus.